1998
DOI: 10.1177/103841119803600103
|View full text |Cite
|
Sign up to set email alerts
|

Costing Turnover: Implications of Work/ Family Conflict at Management Level

Abstract: Workyforce demographics are changing and increasing in diversity. More women are entering the workforce and successfully attaining management positions. Many women choose to postpone child-rearing until their careers have been established and the decision to return to the same employer after childbirth is dependent on the ability to balance family and work commitments. An organization's need to attract and retain valued employees in a highly competitive labour market is a strong motivating factor for increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 36 publications
1
32
0
2
Order By: Relevance
“…Therefore, organizations increasingly implement work-life balance policies to recruit, motivate and retain employees (Cappelli 2000;Friedman and Greenhaus 2000;McCracken 2000), since it leads to higher levels of organizational and market performance (Perry-Smith and Blum 2000), reduced absenteeism and less turnover (Abbott, de Cieri and Iverson 1998). The two factors 'flexible working hours' and 'working schedule' representing work -life balance ranked fifth and sixth.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, organizations increasingly implement work-life balance policies to recruit, motivate and retain employees (Cappelli 2000;Friedman and Greenhaus 2000;McCracken 2000), since it leads to higher levels of organizational and market performance (Perry-Smith and Blum 2000), reduced absenteeism and less turnover (Abbott, de Cieri and Iverson 1998). The two factors 'flexible working hours' and 'working schedule' representing work -life balance ranked fifth and sixth.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, over recent decades 240 The International Journal of Human Resource Management there have been signi® cant changes which challenge traditional management approaches and bring new demands for employers and employees (Lewis and Cooper, 1995). Management strategies which endeavour to address the need for apparent lack of ® t' between work demands and the new diversity of workforce characteristics are emerging, although progress has been somewhat piecemeal (Abbott et al, 1998;Spearritt and Edgar, 1994). Similar arguments of non-linearity in convergence and divergence could be applied with reference to micro-level variables, if one considers theories of acculturation in organizations and society in general (Tung, 1993).…”
Section: Questioning the Dynamicsmentioning
confidence: 97%
“…First, although empirical studies have suggested that family-friendly policies such as a flexible work arrangements increase employees' satisfaction and decrease turnover intention (Abbott, De Cieri, & Iverson, 1998;Brough, O'Driscoll, & Kalliath, 2005;Timms et al, 2015), the mechanisms explaining how this relationship works remain unknown. Thus, this study examines how family-friendly HRM practices influence employees' attitudes by identifying the mediation effect of work-family enrichment.…”
Section: Introductionmentioning
confidence: 98%